1986
DOI: 10.1136/bmj.292.6532.1369
|View full text |Cite
|
Sign up to set email alerts
|

Why are patients with acute stroke admitted to hospital?

Abstract: Data on 515 consecutive patients registered with the Oxfordshire Community Stroke Project were used to compare the characteristics of those patients who were admitted to hospital within one month after their first stroke with those who remained in the community during that time. Twenty eight patients had their stroke while in hospital for other conditions, and ofthe remaining 487, 266 were admitted. Though patients with a severe neurological deficit were significantly more likely to be admitted, 47 out of 202 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(41 citation statements)
references
References 3 publications
2
38
0
1
Order By: Relevance
“…Additionally, physicians tend not to hospitalize older patients. 20 This practice can induce a bias observed in institutional studies that tend to include younger patients and more severe stroke cases. 7 Even though the Matão population cannot represent the whole Brazilian population in terms of lifestyles and genetic aspects, at least in age distribution the Matão population reflects the same proportion as seen in the country (Figure).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, physicians tend not to hospitalize older patients. 20 This practice can induce a bias observed in institutional studies that tend to include younger patients and more severe stroke cases. 7 Even though the Matão population cannot represent the whole Brazilian population in terms of lifestyles and genetic aspects, at least in age distribution the Matão population reflects the same proportion as seen in the country (Figure).…”
Section: Discussionmentioning
confidence: 99%
“…The need to relieve the family of caregiver responsibility has been found to be a reason for institutionalization of stroke patients. 30 Earlier data collection, ie, after discharge, might have revealed higher levels or other types of burden. 6,8 More research is needed on the dynamic aspects of caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands approximately 70% of all stroke patients are admitted to the hospital. 29 Since hospitalized patients have shown to be patients with more severe strokes, 29,30 a community-based study might have revealed lower levels of caregiving burden. Second, generalization may be affected by selection bias caused by nonresponse (52 partners, 30%).…”
Section: Discussionmentioning
confidence: 99%
“…Although these figures show a slight decline in the number of caregivers in the UK, they also show an increase in the number of carers providing support for 20 hours or more every week from 1.5 million to 1.7 millioa Parker (1985) estimated that one and a quarter million people living in Britain care for disabled or elderly people living in the community. It has been documented that between 10 and 50% of stroke patients are cared for at home without ever being admitted to hospital (Bamford et al, 1986;Wade and Langton-Hewer, 1985). The variability in estimates might be due to regional differences in notification systems and hospital referral or differences in the definition and diagnosis of stroke.…”
Section: Prevalence Of Informal Caregivingmentioning
confidence: 99%